Flaky cellulose composite material and preparation method thereof

By combining the composite material preparation method of cellulose fibers, nanofibers, nanocrystals and natural latex, the problems of cellulose are solved and the processing performance are insufficient, and soft, dense and degradable sheet cellulose composite material is realized. The preparation of the material improves the strength and processability.

CN119286065APending Publication Date: 2025-01-10SHANDONG SENXIN ENVIRONMENTAL PROTECTION TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411393219.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Due to the large amount of intramolecular and intermolecular hydrogen bonds and high crystallinity, cellulose materials are difficult to dissolve and do not have melting characteristics, which limits their plasticity and secondary processing properties.

Method used

The preparation method of sheet-like cellulose composite materials, including the combination of raw materials such as cellulose fibers, cellulose nanofibers, cellulose nanocrystals, natural latex and inorganic mineral powder, is formed by specific solvent systems and treatment conditions. The cellulose dissolved solution is prepared by stirring, aging and calendering extrusion, etc., to improve the density and strength of the material.

Benefits of technology

The secondary processing and molding of cellulose is achieved, and the products produced are soft, rich in material sources, long service life and can be completely degraded independently. The supplementary effect of cellulose nanofibers in the system improves the density and strength of the material.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a flaky cellulose composite material and a preparation method thereof. The flaky cellulose composite material comprises the following raw materials in parts by mass: 10-60 parts of cellulose fibers; 1 to 10 parts of cellulose nanofiber; 10 to 50 parts of cellulose nanocrystal; 10 to 60 parts of a cellulose dissolving solution; 1-10 parts of natural latex; and 2 to 15 parts of inorganic mineral powder. According to the invention, the cellulose dissolving solution and the cellulose are compounded, and all the raw materials of the main body are based on the cellulose, so that the cellulose has the possibility of secondary processing and forming. The product prepared by the method is soft, rich in material source and long in service life, and can be completely and autonomously degraded.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a sheet-like cellulose composite material and a preparation method thereof. Background Art

[0002] Cellulose is the most abundant natural polymer material in nature, and its sources are wide, including trees, bamboo, cotton, wheat straw, rice straw and sugarcane bagasse, which are its main sources. In addition, it has very good renewable and biodegradable properties, so cellulose can have a good application market in terms of sustainable development and environmental protection. In addition to the most basic household paper, specialty paper, textile products, and cellulose ethers, cellulose is also widely used in many fields such as medicine, food, and cosmetics. However, the large number of intramolecular and intermolecular hydrogen bonds and high crystallinity in cellulose make cellulose difficult to dissolve and have no melting properties, which greatly limits the plasticity and secondary processing properties of cellulose materials.

[0003] Cellulose dissolution and regeneration technology provides a way for the plastic processing of cellulose. Cellulose can be dissolved in specific solvents and conditions to generate cellulose solution. Cellulose solution has unique regeneration characteristics. It only needs to be treated with specific chemical reagents or chemical processes to regenerate regenerated cellulose products. Currently, commercial regenerated cellulose products are limited to the regeneration preparation of pure cellulose solution, such as regenerated cellulose fiber (lyocell, viscose fiber), regenerated cellulose film (cellophane), etc. In addition, there are no related products related to cellulose solution derivatives. Summary of the invention

[0004] In order to solve the above problems, on the one hand, the present application discloses a sheet-like cellulose composite material, comprising the following raw materials in parts by weight:

[0005] Cellulose fiber: 10-60 parts;

[0006] Cellulose nanofibers: 1-10 parts;

[0007] Cellulose nanocrystals: 10-50 parts;

[0008] Cellulose dissolving solution: 10-60 parts;

[0009] Natural rubber latex: 1-10 parts;

[0010] Inorganic mineral powder: 2-15 parts. This application compounds cellulose dissolving liquid with cellulose, and the main raw materials are all based on cellulose, making it possible for cellulose to be processed and molded for the second time. The product made by this method is soft, has rich material sources, has a long service life, and can be completely self-degradable.

[0011] Preferably, the following raw materials are also included in parts by weight:

[0012] Cross-linking agent: 0.5-5 parts;

[0013] Pigment: 0.1-1.0 parts. The cellulose nanofibers of the present application play a complementary role to the cellulose fibers and cellulose nanocrystals in the system, and their presence makes the system denser and stronger.

[0014] Preferably, the cellulose dissolving solution is obtained in the following manner:

[0015] Placing pulp in a specific solvent system, wherein the mass of the pulp input accounts for 5 to 10 wt% of the total mass of the specific solvent system;

[0016] The specific solvent system is an alkali / urea / water system, wherein the mass fraction of NaOH is 6-8wt%, and the mass fraction of urea is 6-8wt%. The solvent system is precooled to -12°C to -7°C, the pulp is added in batches, and then stirred for 45-60 minutes to obtain a cellulose solution;

[0017] The pulp is cotton pulp or wood pulp.

[0018] Preferably, the cellulose nanocrystals are obtained in the following manner:

[0019] The pulp is placed in a sulfuric acid solution with a mass fraction of 40-70wt%, the mass of the pulp is 5-10% of the mass of the sulfuric acid solution, the reaction temperature is 50-105°C, the reaction is stirred for 2-3 hours, then neutralized and washed, homogenized at 500-900bar for 1-3 times, and concentrated to obtain a cellulose nanocrystal slurry with a solid content of 15-25wt%.

[0020] Preferably, the fiber length of the cellulose nanofibers is 100 to 500 μm and the diameter is 10 to 50 nm;

[0021] The cellulose fiber is one or more of cotton fiber, paper mulberry fiber, bamboo fiber and hemp fiber, and the fiber length is 2 to 20 mm and the diameter is 20 to 1000 μm.

[0022] Preferably, the solid content of the natural latex is 55-65wt%, and the natural latex contains 0.5-1wt% ammonia water;

[0023] The inorganic mineral powder is a mixture of one or more of quartz sand, talc, montmorillonite, wollastonite, kaolin, magnesium hydroxide and mica, and the particle size is between 800 and 1500 meshes.

[0024] Preferably, the cross-linking agent is a mixture of one or more of bentonite, polyvinyl alcohol, borax, starch, polyacrylamide, waterborne polyurethane, starch, ethylene glycol, polyvinyl alcohol, polypyrrolidone, and glycerol;

[0025] The pigment is a mixture of one or more of carbon black, carbon nanotubes, active dyes and acrylic dyes.

[0026] On the other hand, the present application discloses a method for preparing a cellulose composite material, comprising the following steps:

[0027] The cellulose dissolving solution is mixed with natural rubber latex, cellulose fibers, cellulose nanofibers and cellulose nanocrystals and stirred evenly;

[0028] Then add inorganic mineral powder, cross-linking agent and pigment and mix evenly;

[0029] Then stir and age for 3 to 5 hours under vacuum and 0 to 10°C;

[0030] Then, under vacuum conditions, the temperature is naturally raised to 20-35°C, and then stirred and aged for 5-10 hours to obtain the original slurry after degassing;

[0031] The original slurry is calendered and extruded to obtain a sheet material to obtain a composite material. In the aging process of the present application, the cellulose nanocrystals will still partially dissolve due to their short size, and the cellulose nanofibers are in the form of long fibers, which will be more difficult to dissolve than cellulose nanocrystals. After the aging is completed, the dissolved part, the undissolved part and the part in between will form a cellulose system with a more uniform distribution from the molecular level to the micron level, and the density of the product will be correspondingly improved.

[0032] When cellulose dissolves, the lower the temperature, the higher the dissolution rate and solubility. Therefore, in the first step of aging, by reasonably controlling the system temperature and time, the morphology of cellulose nanocrystals and cellulose nanofibers during the aging process can be regulated. Sheet products require strength and softness, so during the aging process, it is necessary to control the partial dissolution process of cellulose nanocrystals while ensuring the long fiber morphology of cellulose nanofibers as much as possible.

[0033] Therefore, the temperature of 0-10℃ was selected, the dissolution process of cellulose nanocrystals was weak, and only local microfibrils of cellulose nanofibers were dissolved, and more of the fiber surface was roughened. The surface roughening of cellulose nanofibers also provided a stable anchor point for regeneration, further improving the strength of the regenerated sample.

[0034] Preferably, the composite material is immersed in a coagulation bath, and after the reaction is completed, it is soaked in clean water to rinse off the residual sulfuric acid and salt to obtain a regenerated and cured composite material; the cured composite material is dried to obtain a dried composite material, and the drying temperature is 50-90°C.

[0035] Preferably, the coagulation bath is an aqueous solution of sulfuric acid and sodium sulfate, wherein the mass fraction of sulfuric acid is 12-15 wt % and the mass fraction of sodium sulfate is 18-25 wt %.

[0036] This application can bring the following beneficial effects:

[0037] 1. This application compounds cellulose dissolving liquid with cellulose, and the main raw materials are all based on cellulose, making it possible for cellulose to be processed and molded for the second time. The product made by this method is soft, has abundant material sources, has a long service life, and can be completely self-degradable.

[0038] 2. The cellulose nanofibers of the present application complement the cellulose fibers and cellulose nanocrystals in the system, and their presence makes the system denser and stronger.

[0039] 3. In the aging process of the present application, under suitable temperature and time conditions, the cellulose nanocrystals and cellulose nanofibers will undergo a process of partial dissolution and surface roughening with weak dissolution behavior. Finally, a highly uniform and dense cellulose system is obtained, and the strength of the regenerated product is also correspondingly improved. DETAILED DESCRIPTION

[0040] In order to clearly illustrate the technical features of this solution, this application is elaborated in detail below through specific implementation methods.

[0041] The present application discloses a sheet-like cellulose composite material and a preparation method thereof. Since it is a material, it relies on its preparation method:

[0042] The steps include:

[0043] S1. preparing cellulose solution and cellulose nanocrystal slurry;

[0044] The cellulose dissolving solution is obtained in the following manner:

[0045] Placing pulp in a specific solvent system, wherein the mass of the pulp input accounts for 5 to 10 wt% of the total mass of the specific solvent system;

[0046] The specific solvent system is an alkali / urea / water system, wherein the mass fraction of NaOH is 6-8wt%, and the mass fraction of urea is 6-8wt%. The solvent system is precooled to -12°C to -7°C, the pulp is added in batches, and then stirred for 45-60 minutes to obtain a cellulose solution;

[0047] The cellulose nanocrystals are obtained in the following manner:

[0048] The pulp is placed in a 40-70wt% sulfuric acid solution with a pulp mass fraction of 5-10%, a reaction temperature of 50-105°C, stirred for reaction for 2-3h, neutralized and washed, homogenized at 500-900bar for 1-3 times, and concentrated to obtain a cellulose nanocrystal slurry with a solid content of 15-25wt%.

[0049] S2. 10 to 60 parts of cellulose solution, 10 to 50 parts of cellulose nanocrystals (i.e., cellulose nanocrystal slurry), 1 to 10 parts of natural rubber latex, 10 to 60 parts of cellulose fibers, and 1 to 10 parts of cellulose nanofibers are mixed and stirred evenly;

[0050] The solid content of the natural latex is 55-65wt%, and the natural latex contains 0.5-1wt% of ammonia water;

[0051] The cellulose fiber is one or more of cotton fiber, paper mulberry fiber, bamboo fiber and hemp fiber, and the fiber length is 2 to 20 mm and the diameter is 20 to 1000 μm.

[0052] The fiber length of the cellulose nanofibers is 100 to 500 μm, and the diameter is 10 to 50 nm;

[0053] S3. Add 2 to 15 parts of inorganic mineral powder, 0.5 to 5 parts of crosslinking agent, and 0.1 to 1 parts of pigment and mix well;

[0054] The inorganic mineral powder is a mixture of one or more of quartz sand, talc, montmorillonite, wollastonite, kaolin, magnesium hydroxide, and mica, and the particle size of the powder is between 800 and 1500 meshes;

[0055] The cross-linking agent is a mixture of one or more of bentonite, polyvinyl alcohol, borax, starch, polyacrylamide, waterborne polyurethane, starch, ethylene glycol, polyvinyl alcohol, polypyrrolidone and glycerol;

[0056] The pigment is a mixture of one or more of carbon black, carbon nanotubes, active dyes and acrylic dyes.

[0057] S4. Then stirring and aging for 3 to 5 hours under vacuum and 0 to 10°C;

[0058] Then, under vacuum conditions, the temperature is naturally raised to 20-35°C, and then stirred and aged for 5-10 hours to obtain the original slurry after degassing;

[0059] S5. The original slurry is calendered and extruded to obtain a sheet material to obtain a composite material.

[0060] S6. Curing treatment:

[0061] The composite material is immersed in a coagulation bath for 40 minutes. After the reaction is completed, it is soaked in clean water to rinse off the residual sulfuric acid and salt to obtain a regenerated and cured composite material. The cured composite material is dried to obtain a dried composite material at a temperature of 50 to 90°C for 3 hours.

[0062] The coagulation bath is an aqueous solution of sulfuric acid and sodium sulfate, wherein the mass fraction of sulfuric acid is 12-15 wt % and the mass fraction of sodium sulfate is 18-25 wt %.

[0063] When implementing it specifically, the following embodiments are performed:

[0064] Embodiment 1:

[0065] S101. Preparing a cellulose solution and a cellulose nanocrystal slurry;

[0066] The cellulose dissolving solution is obtained in the following manner:

[0067] The pulp is placed in a specific solvent system, and the mass of the pulp input accounts for 5wt% of the total mass;

[0068] The specific solvent system is an alkali / urea / water system, wherein the mass fraction of NaOH is 6wt%, and the mass fraction of urea is 6wt%. The solvent system is precooled to -12°C, the pulp is added in batches, and then stirred for 45 minutes to obtain a cellulose solution;

[0069] The cellulose nanocrystals are obtained in the following manner:

[0070] The pulp was placed in a 40wt% sulfuric acid solution with a pulp mass fraction of 5% and a reaction temperature of 50°C. After stirring for 3 hours, the pulp was neutralized and washed, homogenized once at 500bar, and concentrated to obtain a cellulose nanocrystal slurry with a solid content of 15wt%.

[0071] S102. 10 parts of cellulose solution, 10 parts of cellulose nanocrystal slurry, 1 part of natural latex, 10 parts of cellulose fibers, and 1 part of cellulose nanofibers are mixed evenly;

[0072] The solid content of the natural latex is 55wt%, and the natural latex contains 0.5wt% of ammonia water;

[0073] The cellulose fibers are cotton fibers with a fiber length of 2 to 20 mm and a diameter of 20 to 1000 μm.

[0074] The fiber length of the cellulose nanofibers is 100 to 500 μm, and the diameter is 10 to 50 nm;

[0075] S103. Then add 2 parts of inorganic mineral powder, 0.5 parts of crosslinking agent, 0.1 parts of pigment and mix well;

[0076] The inorganic mineral powder is talc, and the particle size of the powder is between 800 and 1500 meshes;

[0077] The cross-linking agent is polyacrylamide;

[0078] The pigment is carbon black.

[0079] S104. Then, under vacuum conditions, the mixture was stirred at 0°C and aged for 5 h, and then naturally heated to 20°C and stirred and aged for 10 h to obtain the original slurry after degassing;

[0080] S105. The original slurry is calendered and extruded to obtain a sheet material, thereby obtaining a composite material. The sheet material has a thickness of 1 mm and a length and width of 500 mm*500 mm.

[0081] S106. Curing treatment:

[0082] The composite material is immersed in a coagulation bath for 40 minutes. After the reaction is completed, it is soaked in clean water to rinse off the residual sulfuric acid and salt to obtain a regenerated and cured composite material. The cured composite material is dried to obtain a dried composite material at a drying temperature of 50°C for 3 hours.

[0083] The coagulation bath is an aqueous solution of sulfuric acid and sodium sulfate, wherein the mass fraction of sulfuric acid is 12 wt % and the mass fraction of sodium sulfate is 18 wt %.

[0084] The sheet material was cut into five groups of 20mm*100mm strips, and then slowly stretched at a rate of 20mm / min by clamping two diagonal strips until the sheet material broke. The maximum tensile force was recorded and the average value of the five groups of samples was obtained to be 302N.

[0085] Embodiment 2:

[0086] S201. Preparing a cellulose solution and a cellulose nanocrystal slurry;

[0087] The cellulose dissolving solution is obtained in the following manner:

[0088] The pulp is placed in a specific solvent system, and the mass of the pulp input accounts for 10wt% of the total mass;

[0089] The specific solvent system is an alkali / urea / water system, wherein the mass fraction of NaOH is 8wt%, and the mass fraction of urea is 8wt%. The solvent system is precooled to -7°C, the pulp is added in batches, and then stirred for 60 minutes to obtain a cellulose solution;

[0090] The cellulose nanocrystals are obtained in the following manner:

[0091] The pulp was placed in a 70wt% sulfuric acid solution with a pulp mass fraction of 10% and a reaction temperature of 105°C. After stirring for 2 hours, the pulp was neutralized and washed, homogenized at 900 bar for 3 times, and concentrated to obtain a cellulose nanocrystal slurry with a solid content of 15wt%.

[0092] S202. 60 parts of cellulose solution, 50 parts of cellulose nanocrystal slurry, 10 parts of natural latex, 60 parts of cellulose fibers, and 10 parts of cellulose nanofibers were mixed and stirred evenly;

[0093] The solid content of the natural latex is 65wt%, and the natural latex contains 1wt% of ammonia water;

[0094] The cellulose fibers are cotton fibers with a fiber length of 2 to 20 mm and a diameter of 20 to 1000 μm.

[0095] The fiber length of the cellulose nanofibers is 100 to 500 μm, and the diameter is 10 to 50 nm;

[0096] S203. Then add 15 parts of inorganic mineral powder, 5 parts of crosslinking agent, 1 part of pigment and mix well;

[0097] The inorganic mineral powder is quartz sand, and the particle size of the powder is between 800 and 1500 meshes;

[0098] The cross-linking agent is polyvinyl alcohol;

[0099] The pigment is a carbon nanotube.

[0100] S204. Then, under vacuum conditions, the mixture was stirred at 10 ° C and aged for 3 h, and then naturally heated to 35 ° C and stirred and aged for 5 h to obtain the original slurry after degassing;

[0101] S205. The original slurry is calendered and extruded to obtain a sheet material, thereby obtaining a composite material. The sheet material has a thickness of 1 mm and a length and width of 500 mm*500 mm.

[0102] S206. Curing treatment:

[0103] The composite material is immersed in a coagulation bath for 40 minutes. After the reaction is completed, it is soaked in clean water to rinse off the residual sulfuric acid and salt to obtain a regenerated and cured composite material. The cured composite material is dried to obtain a dried composite material at a drying temperature of 90°C for 3 hours.

[0104] The coagulation bath is an aqueous solution of sulfuric acid and sodium sulfate, wherein the mass fraction of sulfuric acid is 15wt% and the mass fraction of sodium sulfate is 25wt%.

[0105] The sheet material was cut into five groups of 20mm*100mm strips, and then slowly stretched at a rate of 20mm / min by clamping two diagonal strips until the sheet material broke. The maximum tensile force was recorded and the average value of the five groups of samples was obtained to be 252N.

[0106] Embodiment 3:

[0107] S301. Preparing a cellulose solution and a cellulose nanocrystal slurry;

[0108] The cellulose dissolving solution is obtained in the following manner:

[0109] The pulp is placed in a specific solvent system, and the mass of the pulp input accounts for 5wt% of the total mass;

[0110] The specific solvent system is an alkali / urea / water system, wherein the mass fraction of NaOH is 6wt%, and the mass fraction of urea is 6wt%. The solvent system is precooled to -12°C, the pulp is added in batches, and then stirred for 45 minutes to obtain a cellulose solution;

[0111] The cellulose nanocrystals are obtained in the following manner:

[0112] The pulp was placed in a 40wt% sulfuric acid solution with a pulp mass fraction of 5% and a reaction temperature of 50°C. After stirring for 3 hours, the pulp was neutralized and washed, homogenized once at 500bar, and concentrated to obtain a cellulose nanocrystal slurry with a solid content of 25wt%.

[0113] S302. 10 parts of cellulose solution are introduced into 10 parts of cellulose nanocrystal slurry, 1 part of natural latex, 10 parts of cellulose fibers, and 1 part of cellulose nanofibers and mixed evenly;

[0114] The solid content of the natural latex is 55wt%, and the natural latex contains 0.5wt% of ammonia water;

[0115] The cellulose fibers are cotton fibers with a fiber length of 2 to 20 mm and a diameter of 20 to 1000 μm.

[0116] The fiber length of the cellulose nanofibers is 100 to 500 μm, and the diameter is 10 to 50 nm;

[0117] S303. Then add 2 parts of inorganic mineral powder, 0.5 parts of crosslinking agent, and 0.1 parts of pigment and mix well;

[0118] The inorganic mineral powder is quartz sand, and the particle size of the powder is between 800 and 1500 meshes;

[0119] The cross-linking agent is glycerol;

[0120] The pigment is carbon black.

[0121] S304. Then, under vacuum conditions, the mixture was stirred and aged for 5 h at 0 ° C, and then naturally heated to 20 ° C, stirred and aged for 10 h to obtain the original slurry after degassing;

[0122] S305. The original slurry is calendered and extruded to obtain a sheet material, thereby obtaining a composite material. The sheet material has a thickness of 1 mm and a length and width of 500 mm*500 mm.

[0123] S306. Curing treatment:

[0124] The composite material is immersed in a coagulation bath for 40 minutes. After the reaction is completed, it is soaked in clean water to rinse off the residual sulfuric acid and salt to obtain a regenerated and cured composite material. The cured composite material is dried to obtain a dried composite material at a drying temperature of 50°C for 3 hours.

[0125] The coagulation bath is an aqueous solution of sulfuric acid and sodium sulfate, wherein the mass fraction of sulfuric acid is 12 wt % and the mass fraction of sodium sulfate is 18 wt %.

[0126] The sheet material was cut into five groups of 20mm*100mm strips, and then clamped at two diagonals and slowly stretched at a rate of 20mm / min until the sheet material broke. The maximum tensile force was recorded and the average value of the five groups of samples was obtained to be 218N.

[0127] Comparative Example 1:

[0128] S401. Preparing a cellulose solution;

[0129] The cellulose dissolving solution is obtained in the following manner:

[0130] The pulp is placed in a specific solvent system, and the mass of the pulp input accounts for 5wt% of the total mass;

[0131] The specific solvent system is an alkali / urea / water system, wherein the mass fraction of NaOH is 6wt%, and the mass fraction of urea is 6wt%. The solvent system is precooled to -12°C, the pulp is added in batches, and then stirred for 45 minutes to obtain a cellulose solution;

[0132] S402. 10 parts of cellulose solution, 10 parts of cellulose nanocrystals (commercially available, concentration 15 wt%), 1 part of natural latex, 10 parts of cellulose fibers, and 1 part of cellulose nanofibers are mixed evenly;

[0133] The solid content of the natural latex is 55wt%, and the natural latex contains 0.5wt% of ammonia water;

[0134] The cellulose fibers are cotton fibers with a fiber length of 2 to 20 mm and a diameter of 20 to 1000 μm.

[0135] The fiber length of the cellulose nanofibers is 100 to 500 μm, and the diameter is 10 to 50 nm;

[0136] S403. Then add 2 parts of inorganic mineral powder, 0.5 parts of crosslinking agent, and 0.1 parts of pigment and mix well;

[0137] The inorganic mineral powder is quartz sand, and the particle size of the powder is between 800 and 1500 meshes;

[0138] The cross-linking agent is polyvinyl alcohol;

[0139] The pigment is carbon black.

[0140] S404. Then, under vacuum conditions, the mixture was stirred and aged at 0°C for 5 h, and then naturally heated to 20°C, stirred and aged for 10 h to obtain the original slurry after degassing;

[0141] S405. The original slurry is calendered and extruded to obtain a sheet material, thereby obtaining a composite material. The sheet material has a thickness of 1 mm and a length and width of 500 mm*500 mm.

[0142] S406. Curing treatment:

[0143] The composite material is immersed in a coagulation bath for 40 minutes. After the reaction is completed, it is soaked in clean water to rinse off the residual sulfuric acid and salt to obtain a regenerated and cured composite material. The cured composite material is dried to obtain a dried composite material at a drying temperature of 50°C for 3 hours.

[0144] The coagulation bath is an aqueous solution of sulfuric acid and sodium sulfate, wherein the mass fraction of sulfuric acid is 12 wt % and the mass fraction of sodium sulfate is 18 wt %.

[0145] The sheet material was cut into five groups of 20mm*100mm strips, and then slowly stretched at a rate of 20mm / min by clamping two diagonal strips until the sheet material broke. The maximum tensile force was recorded and the average value of the five groups of samples was 157N.

[0146] Comparative Example 2:

[0147] S501. Preparing a cellulose solution and a cellulose nanocrystal slurry;

[0148] The cellulose dissolving solution is obtained in the following manner:

[0149] The pulp is placed in a specific solvent system, and the mass of the pulp input accounts for 5wt% of the total mass;

[0150] The specific solvent system is an alkali / urea / water system, wherein the mass fraction of NaOH is 6wt%, and the mass fraction of urea is 6wt%. The solvent system is precooled to -12°C, the pulp is added in batches, and then stirred for 45 minutes to obtain a cellulose solution;

[0151] The cellulose nanocrystals are obtained in the following manner:

[0152] The pulp was placed in a 40wt% sulfuric acid solution with a pulp mass fraction of 5% and a reaction temperature of 50°C. After stirring for 3 hours, the pulp was neutralized and washed, homogenized once at 500bar, and concentrated to obtain a cellulose nanocrystal slurry with a solid content of 25wt%.

[0153] S502. 10 parts of cellulose solution, 10 parts of cellulose nanocrystals, 10 parts of cellulose fibers, and 1 part of cellulose nanofibers are mixed evenly;

[0154] The cellulose fibers are cotton fibers with a fiber length of 2 to 20 mm and a diameter of 20 to 1000 μm.

[0155] The fiber length of the cellulose nanofibers is 100 to 500 μm, and the diameter is 10 to 50 nm;

[0156] S503. Then add 2 parts of inorganic mineral powder, 0.5 parts of crosslinking agent, and 0.1 parts of pigment and mix well;

[0157] The inorganic mineral powder is quartz sand, and the particle size of the powder is between 800 and 1500 meshes;

[0158] The cross-linking agent is polyvinyl alcohol;

[0159] The pigment is carbon black.

[0160] S504. Then, under vacuum conditions, the mixture was stirred and aged for 5 h at 0 ° C, and then naturally heated to 20 ° C, stirred and aged for 10 h to obtain the original slurry after degassing;

[0161] S505. The original slurry is calendered and extruded to obtain a sheet material, thereby obtaining a composite material. The sheet material has a thickness of 1 mm and a length and width of 500 mm*500 mm.

[0162] S506. Curing treatment:

[0163] The composite material is immersed in a coagulation bath, and after the reaction is completed, it is soaked in clean water to rinse off the residual sulfuric acid and salt to obtain a regenerated and cured composite material; the cured composite material is dried to obtain a dried composite material, and the drying temperature is 50°C and the time is 3 hours.

[0164] The coagulation bath is an aqueous solution of sulfuric acid and sodium sulfate, wherein the mass fraction of sulfuric acid is 12 wt % and the mass fraction of sodium sulfate is 18 wt %.

[0165] The sheet material was cut into five groups of 20mm*100mm strips, and then clamped at two opposite corners and slowly stretched at a rate of 20mm / min until the sheet material broke. The maximum tensile force was recorded and the average value of the five groups of samples was obtained to be 173N.

[0166] Comparative Example 3:

[0167] S601. 10 parts of cellulose solution (commercially available, concentration 8 wt%), 10 parts of cellulose nanocrystals (commercially available, concentration 15 wt%), 1 part of natural latex, 10 parts of cellulose fibers, and 1 part of cellulose nanofibers are mixed evenly;

[0168] The solid content of the natural latex is 55wt%, and the natural latex contains 0.5wt% of ammonia water;

[0169] The cellulose fibers are cotton fibers with a fiber length of 2 to 20 mm and a diameter of 20 to 1000 μm.

[0170] The fiber length of the cellulose nanofibers is 100 to 500 μm, and the diameter is 10 to 50 nm;

[0171] S602. Add 2 parts of inorganic mineral powder, 0.5 parts of crosslinking agent, and 0.1 parts of pigment and mix well;

[0172] The inorganic mineral powder is quartz sand, and the particle size of the powder is between 800 and 1500 meshes;

[0173] The cross-linking agent is polyvinyl alcohol;

[0174] The pigment is carbon black.

[0175] S603. Then, under vacuum conditions, the mixture was stirred and aged for 5 h at 0 °C, and then naturally heated to 20 °C, stirred and aged for 10 h to obtain the original slurry after degassing;

[0176] S604. The original slurry is calendered and extruded to obtain a sheet material, thereby obtaining a composite material. The sheet material has a thickness of 1 mm and a length and width of 500 mm*500 mm.

[0177] S605. Curing treatment:

[0178] The composite material is immersed in a coagulation bath for 40 minutes. After the reaction is completed, it is soaked in clean water to rinse off the residual sulfuric acid and salt to obtain a regenerated and cured composite material. The cured composite material is dried to obtain a dried composite material at a drying temperature of 50°C for 3 hours.

[0179] The coagulation bath is an aqueous solution of sulfuric acid and sodium sulfate, wherein the mass fraction of sulfuric acid is 12 wt % and the mass fraction of sodium sulfate is 18 wt %.

[0180] The sheet material was cut into five groups of 20mm*100mm strips, and then clamped at two diagonals and slowly stretched at a rate of 20mm / min until the sheet material broke. The maximum tensile force was recorded and the average value of the five groups of samples was obtained to be 140N.

[0181] Comparative Example 4:

[0182] S701. Preparing a cellulose solution and a cellulose nanocrystal slurry;

[0183] The cellulose dissolving solution is obtained in the following manner:

[0184] The pulp is placed in a specific solvent system, and the mass of the pulp input accounts for 5wt% of the total mass;

[0185] The specific solvent system is an alkali / urea / water system, wherein the mass fraction of NaOH is 6wt%, and the mass fraction of urea is 6wt%. The solvent system is precooled to -12°C, the pulp is added in batches, and then stirred for 45 minutes to obtain a cellulose solution;

[0186] The cellulose nanocrystals are obtained in the following manner:

[0187] The pulp was placed in a 40wt% sulfuric acid solution with a pulp mass fraction of 5% and a reaction temperature of 50°C. After stirring for 3 hours, the pulp was neutralized and washed, homogenized once at 500bar, and concentrated to obtain a cellulose nanocrystal slurry with a solid content of 25wt%.

[0188] S702. Mix 10 parts of cellulose solution, 10 parts of cellulose nanocrystals, 1 part of natural latex, 10 parts of cellulose fibers, and 1 part of cellulose nanofibers;

[0189] The solid content of the natural latex is 55wt%, and the natural latex contains 0.5wt% of ammonia water;

[0190] The cellulose fibers are cotton fibers with a fiber length of 2 to 20 mm and a diameter of 20 to 1000 μm.

[0191] The fiber length of the cellulose nanofibers is 100 to 500 μm, and the diameter is 10 to 50 nm;

[0192] S703. Then add 2 parts of inorganic mineral powder, 0.5 parts of crosslinking agent, and 0.1 parts of pigment and mix well;

[0193] The inorganic mineral powder is talc, and the particle size of the powder is between 800 and 1500 meshes;

[0194] The cross-linking agent is polyacrylamide;

[0195] The pigment is carbon black.

[0196] S704. The slurry is calendered and extruded to obtain a sheet material, thereby obtaining a composite material. The sheet material has a thickness of 1 mm and a length and width of 500 mm*500 mm.

[0197] S705. Curing treatment:

[0198] The composite material is immersed in a coagulation bath for 40 minutes. After the reaction is completed, it is soaked in clean water to rinse off the residual sulfuric acid and salt to obtain a regenerated and cured composite material. The cured composite material is dried to obtain a dried composite material at a drying temperature of 50°C for 3 hours.

[0199] The coagulation bath is an aqueous solution of sulfuric acid and sodium sulfate, wherein the mass fraction of sulfuric acid is 12 wt % and the mass fraction of sodium sulfate is 18 wt %.

[0200] The sheet material was cut into five groups of 20mm*100mm strips, and then clamped at two diagonals and slowly stretched at a rate of 20mm / min until the sheet material broke. The maximum tensile force was recorded and the average value of the five groups of samples was obtained to be 144N.

[0201] The above are only embodiments of the present application and are not intended to limit the present application. For those skilled in the art, the present application may have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application should be included within the scope of the claims of the present application.

Claims

1. A sheet-like cellulose composite material, characterized in that: Including the following raw materials by mass: Cellulose fiber: 10-60 parts; Cellulose nanofibers: 1-10 parts; Cellulose nanocrystals: 10-50 parts; Cellulose dissolving solution: 10-60 parts; Natural rubber latex: 1-10 parts; Inorganic mineral powder: 2 to 15 parts.

2. The sheet-like cellulose composite material according to claim 1, characterized in that: It also includes the following raw materials in parts by weight: Cross-linking agent: 0.5-5 parts; Pigment: 0.1~1.0 part.

3. The sheet-like cellulose composite material according to claim 2, characterized in that: The cellulose dissolving solution is obtained in the following manner: Placing pulp in a specific solvent system, wherein the mass of the pulp put in accounts for 5-10wt% of the total mass of the specific solvent system; The specific solvent system is an alkali / urea / water system, wherein the mass fraction of NaOH is 6-8wt%, and the mass fraction of urea is 6-8wt%; the specific solvent system is precooled to -12°C to -7°C, the pulp is added in batches, and then stirred for 45-60 minutes to obtain a cellulose solution; The pulp is cotton pulp or wood pulp.

4. The sheet-like cellulose composite material according to claim 3, characterized in that: The cellulose nanocrystals are obtained in the following manner: The pulp is placed in a sulfuric acid solution with a mass fraction of 40-70wt%, the mass of the pulp is 5-10% of the mass of the sulfuric acid solution, the reaction temperature is 50-105°C, the reaction is stirred for 2-3 hours, then neutralized and washed, homogenized at 500-900bar for 1-3 times, and concentrated to obtain a cellulose nanocrystal slurry with a solid content of 15-25wt%.

5. The sheet-like cellulose composite material according to claim 1, characterized in that: The fiber length of the cellulose nanofibers is 100 to 500 μm, and the diameter is 10 to 50 nm; The cellulose fiber is one or more of cotton fiber, paper mulberry fiber, bamboo fiber and hemp fiber, and the fiber length is 2 to 20 mm and the diameter is 20 to 1000 μm.

6. The sheet-like cellulose composite material according to claim 1, characterized in that: The solid content of the natural latex is 55-65wt%, and the natural latex contains 0.5-1wt% of ammonia water; The inorganic mineral powder is a mixture of one or more of quartz sand, talc, montmorillonite, wollastonite, kaolin, magnesium hydroxide and mica, and the particle size of the powder is between 800 and 1500 meshes.

7. The sheet-like cellulose composite material according to claim 2, characterized in that: The cross-linking agent is a mixture of one or more of bentonite, polyvinyl alcohol, borax, starch, polyacrylamide, waterborne polyurethane, starch, ethylene glycol, polyvinyl alcohol, polypyrrolidone and glycerol; The pigment is a mixture of one or more of carbon black, carbon nanotubes, active dyes and acrylic dyes.

8. A method for producing the cellulose composite material according to claim 4, characterized in that: The steps include: The cellulose dissolving solution is mixed with natural rubber latex, cellulose fibers, cellulose nanofibers and cellulose nanocrystals and stirred evenly; Then add inorganic mineral powder, cross-linking agent and pigment and mix evenly; Then stir and age for 3 to 5 hours under vacuum and 0 to 10°C; Then, under vacuum conditions, the temperature is naturally raised to 20-35°C, and then stirred and aged for 5-10 hours to obtain the original slurry after degassing; The original slurry is calendered and extruded to obtain a sheet material, thereby obtaining a composite material.

9. The method for preparing a sheet-like cellulose composite material according to claim 8, characterized in that: The composite material is immersed in a coagulation bath, and after the reaction is completed, it is soaked in clean water to rinse off the residual sulfuric acid and salt to obtain a regenerated and cured composite material; the cured composite material is dried to obtain a dried composite material, and the drying temperature is 50-90°C.

10. The method for preparing a sheet-like cellulose composite material according to claim 9, characterized in that: The coagulation bath is an aqueous solution of sulfuric acid and sodium sulfate, wherein the mass fraction of sulfuric acid is 12-15 wt % and the mass fraction of sodium sulfate is 18-25 wt %.